Penguatan Partisipasi Masyarakat dalam Meningkatkan Kepemilikan Akta Kelahiran pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sikka - Fransiskus Steven; Elisabeth Luju; Emilianus Eo Kutu Goo (BADAN PENERBIT STIEPARI PRESS, 2025)
This reseach aims to find out how strengthen community participation in increasing ownership of birth certificates at the Sikka Regency Population and Civil Resgistration Services. To identify problems, this research uses qualitative research. This data collection techniques use observation, interviews, and documentation. It can be concluded that the factors that influence the deline in community participation are caused by community awareness, lack of community knowledge, living environment, and limited access. Efforts to increase community participation include providing outreach, improving services programs, and collaborating with community leaders and educational institutions such as kindergartens